2007
DOI: 10.1016/j.bmcl.2007.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-containing aryloxyethyl thiocyanate derivatives are potent inhibitors of Trypanosoma cruzi and Toxoplasma gondii proliferation

Abstract: As a part of our project aimed at developing new safe chemotherapeutic and chemoprophylactic agents against tropical diseases, fluorine-containing drugs structurally related to 4-phenoxyphenoxyethyl thiocyanate (1) were designed, synthesized and evaluated as antiproliferative agents against Trypanosoma cruzi, the parasite responsible of American trypanosomiasis (Chagas' disease) and Toxoplasma gondii, the etiological agent of toxoplasmosis. This thiocyanate derivative had previously proven to be an effective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 39 publications
1
28
1
Order By: Relevance
“…The tetrahydropyranyl precursor 10 of 13 was devoid of biological activity against T. cruzi (amastigotes) proliferation. This observation was not in agreement with our previous results in other closely related compounds, where the biological activity of WC-9 analogues correlated quite well with the activity exhibited by their synthetic tetrahydropyranyl ether precursors when bonded to the same aromatic skeleton [22,23,32]. Compound 13 was also a potent inhibitor of T. gondii (tachyzoites) growth possessing an ED 50 values at the very low micromolar level (2.0 μM).…”
Section: Resultscontrasting
confidence: 73%
See 2 more Smart Citations
“…The tetrahydropyranyl precursor 10 of 13 was devoid of biological activity against T. cruzi (amastigotes) proliferation. This observation was not in agreement with our previous results in other closely related compounds, where the biological activity of WC-9 analogues correlated quite well with the activity exhibited by their synthetic tetrahydropyranyl ether precursors when bonded to the same aromatic skeleton [22,23,32]. Compound 13 was also a potent inhibitor of T. gondii (tachyzoites) growth possessing an ED 50 values at the very low micromolar level (2.0 μM).…”
Section: Resultscontrasting
confidence: 73%
“…We have established a rigorous SAR studies on WC-9 chemical structure finding that the phenoxyethyl thiocyanate moiety, which is colored in red in Figure 1, can be considered as the structure of the pharmacophore [21-23,31,32]. However, pharmacokinetic properties of this representative drug still should be improved.…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, both of these compounds, 2 and 3 , are significantly more potent than WC-9 in in vitro assays (Figure 1). [23] …”
Section: Rationalementioning
confidence: 99%
“…It has been found that growth inhibition of T. cruzi epimastigotes induced by 4-Phenoxyphenoxyethyl thiocyanate also known as WC-9 was associated with a reduction in the content of the parasite's endogenous sterols due to a specific blockade of their de novo synthesis at the level of squalene synthase [73]. Previous studies on WC-9 have indicated that structural variation at the B ring had no influence on biological action [74,74], it was thought that the introduction of a fluorine atom at the B ring would benefit biological activity.…”
Section: Squalene Synthase (Sqs)mentioning
confidence: 99%